A numerical coupling model for a multibody system with multiple lubricated clearance joints - Zhao, Bo (2018)
In machines and mechanisms, most of the clearance joints are designed to operate with lubricant fluid, which is an effective way of ensuring better performance of the mechanical systems. The differently located lubricated joints interact with each other, influencing the total performances of the mechanical system. In this study, a numerical coupling model for the dynamics and lubrication analyses of the multibody system with multiple lubricated clearance joints is established. This approach couples the dynamics model of the multibody system with the lubrication models of translational and revolute clearance joints. The dynamics model is established by the Lagrange’s method, while The lubrication models are solved using the finite element method. The hydrodynamic forces built up by the lubricant fluid are evaluated from the motion states of the system and then input into dynamics model of the multibody system. Finally, the proposed approach is applied to a four-stroke gasoline engine with the lubricated piston skirt-liner subsystem and lubricated bearing at the big end of the connecting rod.